Respuestas
Respuesta dada por:
2
Método de reducción
3p - 11q = 5 (1)
3p + 4q = 1 (2) multiplico (2) por (-1) queda
3p - 11q = 5 (1)
-3p - 4q = -1 (2)
----------------------
0 - 15q = 4
q = -(4/15) (3)
Reemplazo (3) en (2)
3p + 4q = 1 (2)
3p +4(-4/15) = 1
3p -(16/15) = 1
3p = 1 + (16/15)
p = (31/15)/3
p = (31/45)
Por tanto
p = (31/45)
q = -(4/15)
Espero te sirva de ayuda
3p - 11q = 5 (1)
3p + 4q = 1 (2) multiplico (2) por (-1) queda
3p - 11q = 5 (1)
-3p - 4q = -1 (2)
----------------------
0 - 15q = 4
q = -(4/15) (3)
Reemplazo (3) en (2)
3p + 4q = 1 (2)
3p +4(-4/15) = 1
3p -(16/15) = 1
3p = 1 + (16/15)
p = (31/15)/3
p = (31/45)
Por tanto
p = (31/45)
q = -(4/15)
Espero te sirva de ayuda
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años